2004
DOI: 10.1128/mcb.24.5.2118-2131.2004
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Boundaries of Transcriptionally Silent Chromatin by Nucleosome-Excluding Structures

Abstract: The eukaryotic genome is divided into chromosomal domains of distinct gene activities. Transcriptionally silent chromatin tends to encroach upon active chromatin. Barrier elements that can block the spread of silent chromatin have been documented, but the mechanisms of their function are not resolved. We show that the prokaryotic LexA protein can function as a barrier to the propagation of transcriptionally silent chromatin in yeast. The barrier function of LexA correlates with its ability to disrupt local chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 54 publications
(96 reference statements)
11
87
1
Order By: Relevance
“…Specifically, we envision that the nucleosome positioned close to the Abf1p side of the silencer allows or facilitates the Sir complex to start spreading on this side, whereas the lack of a stably positioned nucleosome adjacent to the ORC site reduces the efficiency of initiation of Sir propagation on this side. This hypothesis is based on the fact that nucleosomes are both the substrates for the histone deacetylase activity of the Sir complex and also the platform for Sir recruitment, according to the current view of the nucleosome-by-nucleosome propagation of Sir complexes along chromatin (3,13,32). In support of this contention, we have demonstrated that Sir3p preferentially associates with sequences on the Abf1p side of the HMR-E silencer (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Specifically, we envision that the nucleosome positioned close to the Abf1p side of the silencer allows or facilitates the Sir complex to start spreading on this side, whereas the lack of a stably positioned nucleosome adjacent to the ORC site reduces the efficiency of initiation of Sir propagation on this side. This hypothesis is based on the fact that nucleosomes are both the substrates for the histone deacetylase activity of the Sir complex and also the platform for Sir recruitment, according to the current view of the nucleosome-by-nucleosome propagation of Sir complexes along chromatin (3,13,32). In support of this contention, we have demonstrated that Sir3p preferentially associates with sequences on the Abf1p side of the HMR-E silencer (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…In this manner, the Sir complex is thought to promote its own stepwise (nucleosomeby-nucleosome) propagation along a continuous array of nucleosomes, thereby establishing an extended region of silent chromatin (13). This model is supported by our finding that disrupting the regularity of nucleosomes by nucleosome-excluding structures hinders the spread of silent chromatin (3).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Although the borders of the DNase I-hypersensitive site I were not mapped except for the upstream border on the upper strand, the analysis of the lower strand revealed that the hypersensitive region included at least 250 bases. This extensive region of hypersensitivity is probably nucleosome-free (30), and it has been proposed that the absence of nucleosomes from insulators is important for their function (33,34). Within the hypersensitivite site, there were two cold spots or areas of relative resistance around the CCAAT box and around the CTCF binding motif but not around the thyroid hormone response element.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which such spreading is blocked has been attributed to targeted recruitment of HAT activity to boundary elements, with histone acetylation acting as a chain terminator for the heterochromatic modification pattern. An alternative model proposes that a short (100 -300 bp) nucleosome-free region is formed at the boundary, which the processive mechanism of heterochromatin spreading cannot span (39).…”
Section: Minireview: Formation and Function Of Hyperacetylated Domainmentioning
confidence: 99%